Impact of Participation in a Telestroke Network on Clinical Outcomes: Evidence From the Georgia Coverdell Acute Stroke Registry. Issue 1 (January 2019) - Zhang, Donglan; Shi, Lu; Ido, Moges S.; Green, Dale E.; Li, Yan; Su, Dejun; Hess, David C.
Abstract : Background: A telestroke program, known as the Remote Evaluation for Acute Ischemic Stroke program, has been implemented in Georgia since 2003. This study examined whether a hospital's participation in a telestroke network was associated with improvement in clinical outcomes and quality indicators. Methods and Results: An observational study was conducted using data from the Georgia Coverdell Acute Stroke Registry between September 2005 and September 2016 for patients aged ≥18 years with ischemic stroke. We use a difference-in-differences approach to compare the following clinical outcomes and quality indicators among those admitted at hospitals within and outside of the Remote Evaluation for Acute Ischemic Stroke network: tPA (tissue-type plasminogen activator) use, complications related to tPA use, door-to-needle time, ambulation at discharge, discharge status, and destination. Logistic regression models and a propensity score weighting approach were performed to adjust for patients' age, sex, race, insurance coverage, arrival mode, ambulatory status before the current stroke, stroke severity, medical history, admission time, and hospital bed size. A total of 25 494 patients with ischemic stroke admitted at 15 nonteaching hospitals located outside of the Atlanta metropolitan area were included in the analysis. After propensity score weighting, hospitals participated in a telestroke network was not associated with a significant increase in the rate of tPA use, while it was significantly associated with a modest decline in the rate of complications related to tPA (−5.9%; 95% CI, −9.2% to −2.6%). Telestroke participation showed no significant difference in other clinical outcomes and quality measures except for a marginally significant decrease in in-hospital mortality (−1.1%; 95% CI, −2.2% to −0.1%). Conclusions: Although a slight decrease in tPA complication was observed among hospitals participating in the telestroke network, overall the impact of telestroke participation on a hospital's stroke care quality was not statistically significant based on our observational study. Abstract : Supplemental Digital Content is available in the text.